PENERAPAN MEDIA AUDIO VISUAL BERBANTI MODEL PBL (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK PADA MATA PELAJARAN SISTEM PERNAPASAN MANUSIA DI KELAS V SD NEGERI 152/X SUNGAI SAYANG 2023/2024 - Tiara Puspa Dewi; Sukendro; Muhammad Sofwan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to improve student activity in learning the human respiratory system using the Problem Based Learning (PBL) model assisted by audio-visual media in class V of SD Negeri 152/X Sungai Sayang in the 2023/2024 academic year. This Classroom Action Research (CAR) was conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. The data collected included student activity in asking questions, discussing, and expressing opinions. The results of the study showed a gradual increase in student activity. In the first cycle, student activity was still low with a percentage of asking questions of 48%, discussing 60%, and expressing opinions 40%. In the second cycle, student activity increased to 72%, 80%, and 68% for each aspect. At its peak in the third cycle, student activity reached a high category with a percentage of asking questions of 88%, discussing 92%, and expressing opinions 80%. The use of audio-visual media has proven effective in attracting students' attention and facilitating their understanding of the material. In addition, teacher guidance plays an important role in encouraging students to be more confident and active during learning. The conclusion of this study is that the PBL model assisted by audio-visual media is effective in increasing student activity while helping them understand the material in depth. This approach is recommended to be applied to learning in various other subjects that require interaction and conceptual understanding.